Creating a food tour for millennials in Kallio district - Meriläinen, Ekaterina (2019)
Main idea of the paper is related to food tourism in Helsinki. Main goal and topic of this thesis is creation of a food tour for millennials in Kallio district. Author of the paper created a product type thesis by cooperating with commissioning party Haaga-Helia project “Hungry for Finland”, which is part of Finland’s first food tourism strategy 2015-2020. In theoretical part of thesis, with help of references, main concepts of food tourism were presented. It was important to make benchmarking of already existing food tours to understand what motivates tourists to travel, in such countries like England, Iceland and Japan. Millennials as a customer group are very important for food tourism. Creating a specially tailored food tour for this type of group is essentially important for food tourism in Helsinki. Travelling habits of millennials are different from generation of baby boomers. In theoretical part of thesis, with help of references main characteristics of millennials were described. Author made short description of Kallio area and explained why this particular location can attract millennials to visit. While creating the product, author used method of observation. After choosing locations for the tour, author made visits to that locations. During the visits, author used an observation form that was filled while food testing. Visits were made during April-May of 2019. This form helped to collect important information for creating text of final product. In final product author used a blog type of text to communicate with millennials. In the blog type of text, author was inviting readers to follow her personal journey in Kallio district. Author also took pictures while visiting locations for using it in creating final product. Result of thesis is a four days food tour for millennials in Kallio district. In the tour there were chosen locations that can be interesting to the target group. Among them there were cafés, bistro, bar, restaurant, dinner at the house of local farmer, creative space of an old slaughterhouse, local market and a brewery.